Laser therapy for stress urinary incontinence in women: a systematic review and meta-analysis - Alkhamis, Fatimah Hussain (International Journal Of Community Medicine And Public Health, 2025)
Stress urinary incontinence (SUI) is a prevalent condition among women, significantly impacting their quality of life. Laser therapy has emerged as a non-invasive treatment option, but its efficacy remains uncertain due to limited evidence. This systematic review and meta-analysis aimed to evaluate the effectiveness of laser therapy in improving SUI symptoms, measured by changes in international consultation on incontinence questionnaire-urinary incontinence short form (ICIQ-UI SF) scores. A comprehensive search was conducted across PubMed, Web of Science, Scopus, Medline, the Cochrane Library, and Google Scholar, yielding 532 records. Six studies, including three randomized controlled trials and three prospective studies, met the inclusion criteria. Data were synthesized using a random-effects model. The meta-analysis included 507 women with SUI. Pooled analysis revealed a statistically significant reduction in ICIQ-UI SF scores following laser therapy, with a mean difference of -2.15 (95% CI: -4.26 to -0.05, p=0.05). Substantial heterogeneity was observed (I²=85%, p<0.00001). Studies with longer follow-up periods, such as Okui, 2019 (mean difference: -4.66, 95% CI: -6.89 to -2.43), demonstrated greater improvements. Funnel plot analysis suggested no significant publication bias. Laser therapy significantly improves SUI symptoms, as evidenced by reductions in ICIQ-UI SF scores. However, variability in treatment protocols and study designs underscores the need for standardized approaches and further research to confirm long-term efficacy.